Bridge Displacement Estimation using Tiltmeter Data - Raka Bagus Panuntun; Akhmad Aminullah; Bambang Suhendro; Panji Krisna Wardana (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
Structural Health Monitoring System (SHMS) works as an efficient platform for monitoring health condition and and deterioration of civil structures during long-term service periods. One of the sensors is currently applied to Soekarno Bridge is tiltmeter. Vertical displacement data are often required to reflect the overall response of bridge span, however the Soekarno Bridge does not have any displacement sensor. On the other hand, the displacement sensor is very costly compared to tiltmeter. A method is proposed to estimate bridge displacement using data that is collected through tiltmeter. The method is using interpolation and numerical integration to evaluate the displacement. The result shows that the result obtained from the proposed method is reliable with accuracy of displacement around 5 mm. Some recommendations for further implementation of the sensors are provided.